2008
DOI: 10.2903/j.efsa.2008.793
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin in flavourings and other food ingredients with flavouring properties ‐ Scientific Opinion of the Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food (AFC)

Abstract: The Panel considered the toxicity studies and the studies on the metabolism of coumarin in humans with CYP2A6 polymorphism that have become available since the last opinion of 2004, as well as clinical studies, and concluded to maintain the TDI of 0.1 mg coumarin/kg bw allocated in the 2004 opinion.Considering the toxicity data on coumarin, including the timing of the onset of liver effects, recovery of these effects after cessation of exposure to coumarin and the elimination half-life, the Panel concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…Taking into consideration that the most sensitive animal species were rats and dogs, based on a two-year dog study, the overall No Observed Adverse Effect Level (NOAEL) for liver toxicity was found to be of 10 mg/kg bw per day. Applying a total safety factor of 100 to this NOAEL (a factor of 10 for potential interspecies variation, together with a factor of 10 for potential interindividual differences in humans), it was concluded that a TDI of 0 -0.1 mg coumarin/kg bw could be established [106,121]. This conclusion was further supported by the German Federal Institute for Risk Assessment (BfR) [122,123].…”
Section: Discussionmentioning
confidence: 92%
“…Taking into consideration that the most sensitive animal species were rats and dogs, based on a two-year dog study, the overall No Observed Adverse Effect Level (NOAEL) for liver toxicity was found to be of 10 mg/kg bw per day. Applying a total safety factor of 100 to this NOAEL (a factor of 10 for potential interspecies variation, together with a factor of 10 for potential interindividual differences in humans), it was concluded that a TDI of 0 -0.1 mg coumarin/kg bw could be established [106,121]. This conclusion was further supported by the German Federal Institute for Risk Assessment (BfR) [122,123].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, although the toxicity of hydroxycoumarins is low, their safety also needs to be carefully considered. European Food Safety Authority (EFSA) suggested that the Tolerable Daily Intake (IDT) of coumarin was 0.1 mg/kg body weight . For food and beverages, in general, the maximum permissible level is 2 mg/kg .…”
Section: Discussionmentioning
confidence: 99%
“…In the aspect of safe cinnamon edibility, coumarin is known to be the main toxic substance present in cinnamon. According to the European Food Safety Authority, the human daily tolerance for coumarin is 0.1 mg/kg [ 46 ]. Among the several commercially available cinnamon species, C. verum contains the lowest content of coumarin: 0.017 mg/g [ 47 ], indicating the edible safety of C. verum and providing strong support for its use as a dietary supplement and drug development.…”
Section: Discussionmentioning
confidence: 99%